Étude contrastive du système des pronoms en français et en roumain (du point de vue du système linguistique et du point de vue socioculturel) - Bălăcescu, Ioana Adriana (Studia Romanica Posnaniensia, 2007)
With regard to the use of pronouns Romanian shares a number of features with other Romance languages in opposition to French and English, due to the linguistic system: the pronouns are not obligatory because of the morphological markedness o f the verbal forms. For reasons linked to the socio-cultural system however the use of pronouns is far more differentiated in Romanian than in any other Romance or Anglo- Saxon language.